Discovering and analyzing the intellectual structure and its evolution of LIS in China, 1998–2007 - Ma, Ruimin (Scientometrics, 2012)
The intellectual structure and its evolution of library and information science (LIS) in China are analyzed with time series data from Chinese Social Sciences Citation Index which is the properest database for ACA practice in the field of social science at present. The result indicates that the subfields of Library and Information Science in China kept changing from 1998 to 2007: some subfields have emerged and developed a lot, e.g., webometrics and competitive intelligence; some subfields maintain, e.g., bibliometrics and intellectual property; and some subfields have begun to decline, e.g., cataloging. Through the comparison with the international LIS, it is found that there are some unique subfields in Chinese LIS from 1998 to 2007, such as competitive intelligence and intellectual property. At the same time, I also suggest that Chinese authors in LIS should pay more attention to the applied research in the future.